Penggunaan XML Database Xindice pada Aplikasi Kriptografi menggunakan Data XML untuk Keamanan Distribusi Data - Edy Winarno (Universitas Stikubank, 2009)
In order to send data or information processed by using cryptography people can use XML(eXtensible Markup Language). XML data are general texts file which consist of several different tagswhich are defined by the XML document maker. In this research, the XML data were processed by usingPassword Based Encryption cryptography. This method consists of encryption and decryption meant toalter plaintext into chipertext which in turn creates chipertext from plaintext by using password key.²The implementation of the program in this research is a prototype of Hospital’s web facilitated withencyption menus and decryption data which are meant to protect the saved data which are in turn accessedand processed by authorized people. The implementation of the program is built as a web application withJava Server Page (JSP) in NetBeans 6.0 with Password Based Encryption cryptography provided by JavaCryptography Extension (JCE).